Sejarah Tumbuh Kembang Industri Informal Berbasis Pertanian di Kabupaten Bandung - Charina, Anne; Kusumo, Rani Andriani Budi; Mukti, Gema Wibawa (Universitas Galuh, 2025)
Informal industry plays an important role in the national economy, especially in developing countries such as Indonesia. Due to its informal nature, the economic activity of informal industries invites many crucial problems. However, what is interesting is why this informal industry activity still exists, even its number is very mushrooming in Indonesia. This research is located in Ciparay, Ibun, and Majalaya Districts, which are the three districts with the largest number of informal industries in Bandung Regency. This study aims to analyze the history of the growth and development of informal agriculture-based industries in Bandung Regency. Using a qualitative approach, data were collected through interviews with 50 informal agricultural-based industry actors. Thematic analysis with N-vivo software version 12 was used to analyze the data obtained. This study reveals that the growth and development of informal agriculture-based industries in Bandung Regency is more based on hereditary factors (continuing family businesses) supported by the strength of capital in building businesses. Informal industry entrepreneurs come from the traditional elite, building businesses independently, without government intervention.